A virtual learning environment development. Some experiences at the University of La Plata - Sanz, Cecilia Verónica (2006)
E-learning is a new and rapidly evolving discipline. Particularly, e-learning environments have become a topic of research and study. This paper presents an investigation related to e-learning and the development of virtual learning environment (WebINFO) made by an interdisciplinary team at the University of La Plata. Some experienceswithin university scope using this kind of technology are also presented.